Do Air Passengers Decide Rationally? Case Study of Travellers on Route Prague-London - Katerina Pojkarova; Dalibor Gottwald (Communications - Scientific letters of the University of Zilina, 2019)
Decision-making is an integral part of every human‘s life, both personal and professional, and today‘s highly globalized world brings many different factors that affect the decision-making process. General economic theory of utility is grounded in the assumption that people make decisions rationally. Recently, however, its limits have been challenged by both scientific and professional public - the theory of rational choice acknowledges only a limited number of factors that influence the decision-making. The aim of the present article is to discover whether the current debate can be applicable to decision-making processes of flight passengers in a case study of travelers on route from Prague to London. The article presents results of a primary research carried out by authors in 2018. The survey set to explore validity of choice theory in the sector of logistics, in particular in decision-making processes of passengers who buy flight ticket on route Prague - London. At the base of result it can be confirmed that the classical theory of rational choice in economical perspective has been proven false. When people‘s behavior, as a result of their decision making, serves as a basis for future predictions of development in a given area, it is essential to take into account other, usually hidden factors, which also affect the decision-making process.